Effects of White Turmeric Infusion on the Liver Cells in Carbon Tetrachloride-Induced Mice - Fitria Oktaviani; RB. Soeherman Herdiningrat; Herry Yulianti (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: The liver is an organ that has important functions in the body. Liver damage can be caused by oxidative stress and free radicals. White turmeric (Curcuma zedoaria L) contains antioxidants that can be used to neutralize the effects of free radicals. This study was conducted to determine the effect of white turmeric infusion on histological appearance of liver cells in male mice induced by carbon tetrachloride (CCl4).Methods: This laboratory experimental study was conducted using male mice (Mus musculus) with Balb/c strain. Thirty-three mice were randomly divided into 3 groups i.e.,group 1 as a control group was given standard food and drink, group 2 was given 10% of CCl4 0.1 ml by intraperitoneal injection on the first day and group 3 was given 10% of CCl4 0.1 mL by ntraperitoneal injection on the first day, followed by the administration of 50% of white turmeric infusion 0.2 mL. Kruskal-Wallis test method was used to analyse the significant differences of the average percentage of damaged liver cells in the group given CCl4 alone with the group given CCl4 and white turmeric infusion and control group.Results: The percentage of damaged liver cells between groups of mice given CCl4 alone and the group given CCl4 followed by white turmeric infusion were respectively(p <0.05) compared to group1.Conclusions: Administration of white turmeric infusion gave an influence by decreasing the percentage of damaged liver cells in CCl4-induced mice. White turmeric can serve as an alternative antioxidants that can be used to neutralize the effects of free radicals. [AMJ.2015;2(4):506–10] DOI: 10.15850/amj.v2n4.498